Non-coding RNAs and HIV: viral manipulation of host dark matter to shape the cellular environment - Barichievy, Samantha; Naidoo, Jerolen; Mhlanga, Musa M. (Frontiers in Genetics, 2015)
On October 28th 1943 Winston Churchill said “we shape our buildings, and afterwards our buildings shape us” (Humes, 1994). Churchill was pondering how and when to rebuild the British House of Commons, which had been destroyed by enemy bombs on May 10th 1941. The old House had been small and insufficient to hold all its members, but was restored to its original form in 1950 in order to recapture the “convenience and dignity” that the building had shaped into its parliamentary members. The circular loop whereby buildings or dwellings are shaped and go on to shape those that reside in them is also true of pathogens and their hosts. As obligate parasites, pathogens need to alter their cellular host environments to ensure survival. Typically pathogens modify cellular transcription profiles and in doing so, the pathogen in turn is affected, thereby closing the loop. As key orchestrators of gene expression, noncoding RNAs provide a vast and extremely precise set of tools for pathogens to target in order to shape the cellular environment. This review will focus on host noncoding RNAs that are manipulated by the infamous intracellular pathogen, the Human Immunodeficiency Virus (HIV). We will briefly describe both short and long host noncoding RNAs and discuss how HIV gains control of these factors to ensure widespread dissemination throughout the host as well as the establishment of lifelong, chronic infection.